2008
DOI: 10.1111/j.1365-2389.2008.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term carbon loss and CO2‐C release of drained peatland soils in northeast Germany

Abstract: Peatlands are common in many parts of the world. Draining and other changes in the use of peatlands increase atmospheric CO 2 concentration. If we are to make reliable quantitative predictions of that effect, we need good information on the CO 2 emission rates from peatlands. The present study uses two different methods for predicting CO 2 -C release of peatland soils: (i) a 40-year field investigation of balancing organic carbon stocks and (ii) short-term CO 2 -C release rates from laboratory experiments. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 37 publications
3
30
0
8
Order By: Relevance
“…Drainage of peat soils results in mineralization, shrinkage and subsidence which also changes the bulk density. The observed bulk density of the topsoil in our study was found to be about twice as high compared with the 45-55 cm layer, a trend similar to the findings of Schothorst (1977) and Kluge et al (2008). This higher bulk density closer to the soil surface will be partly due to shrinkage and partly due to the anthropogenic addition of solid sand size particles.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Drainage of peat soils results in mineralization, shrinkage and subsidence which also changes the bulk density. The observed bulk density of the topsoil in our study was found to be about twice as high compared with the 45-55 cm layer, a trend similar to the findings of Schothorst (1977) and Kluge et al (2008). This higher bulk density closer to the soil surface will be partly due to shrinkage and partly due to the anthropogenic addition of solid sand size particles.…”
Section: Discussionsupporting
confidence: 74%
“…This estimate approaches the observations of Kluge et al (2008) for extensively managed grasslands with shallow groundwater tables in East Germany. For recent decades, they reported a mean decrease in peat thickness of 2.7 mmyr −1 for peatland soils with groundwater levels fluctuating between 50 and 70 cm below the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was used by Leifeld et al (2011a), who estimated mean carbon loss rates ranging from +140 to +490 g C m −2 a −1 for two drained pre-Alpine mountain bogs. Kluge et al (2008) modeled a larger mean annual peat-carbon loss of about +700 g C m −2 a −1 for an agricultural peatland in northeastern Germany. Reported soil emission rates of forested peatlands span a wide range, including our rough estimate.…”
Section: Long-term Carbon Balancementioning
confidence: 99%
“…Für ein flussnahes Niedermoor in Nordostdeutschland wurden durchschnittliche Abbauraten der organischen Bodenhorizonte von 0,7 cm Mächtigkeit pro Jahr über einen Zeitraum von 40 Jahren gemessen (Kluge et al 2008). Für ein zukünftiges Klima mit im Schnitt 2 °C höheren Temperaturen und 20 % ge-ringerem Niederschlag im Sommerhalbjahr sagt dieselbe Studie eine Zunahme der Abbaurate um ca.…”
Section: Mooreunclassified